2017
DOI: 10.1002/nau.23224
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐3 adrenergic receptor is expressed in acetylcholine‐containing nerve fibers of the human urinary bladder: An immunohistochemical study

Abstract: We demonstrated that β3AR is abundantly located in acetylcholine-containing nerve fibers. These findings have important consequences to understand the mechanism of action of β3AR agonists currently used for the treatment of OAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 23 publications
2
50
0
Order By: Relevance
“…A recent study by Coelho et al. found that β3‐ARs were primarily expressed in nerve fibres in the mucosa and muscle layers of the bladder but not in urothelium or smooth muscle; however, Silva et al. showed that β3‐AR immunofluorescence was higher in the smooth muscle layer, compared with the urothelium and sub‐urothelium.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study by Coelho et al. found that β3‐ARs were primarily expressed in nerve fibres in the mucosa and muscle layers of the bladder but not in urothelium or smooth muscle; however, Silva et al. showed that β3‐AR immunofluorescence was higher in the smooth muscle layer, compared with the urothelium and sub‐urothelium.…”
Section: Discussionmentioning
confidence: 98%
“…The body of the human bladder receives a relatively sparse innervation by noradrenergic nerves [11], and Coelho et al [12] observed that numerous smooth muscle areas were without any tyrosine-hydroxylase (key enzyme involved in noradrenaline synthesis) immunoreactive fibres. The density of noradrenergic nerves increases markedly toward the bladder neck, where the smooth muscle receives a dense noradrenergic nerve supply, particularly in the male [11].…”
Section: Adrenergic Nerves In the Bladder And Urethramentioning
confidence: 99%
“…The density of noradrenergic nerves increases markedly toward the bladder neck, where the smooth muscle receives a dense noradrenergic nerve supply, particularly in the male [11]. Noradrenergic nerves can be found also in the lamina propria of the bladder, only some of which are related to the vascular supply [11,12]. …”
Section: Adrenergic Nerves In the Bladder And Urethramentioning
confidence: 99%
See 2 more Smart Citations